The depression anxiety stress scales (DASS-21): an Indonesian validation measure of the depression anxiety stress - Ifdil, Ifdil; Syahputra, Yuda; Fadli, Rima Pratiwi; Zola, Nilma; Putri, Yola Eka; Amalianita, Berru; Rangka, Itsar Bolo; Suranta, Kadek; Zatrahadi, M. Fahli; Sugara, Gian Sugiana; Situmorang, Dominikus David Biondi; Fitria, Linda (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2020)
This study attempts to evaluate the Indonesian adaptation of the DASS-21, a scale adapted from Peter F. and Sydney H. Lovibond 1995 to assess levels of stress, anxiety, and depression. Multistage random sampling taking from 1478 Indonesian. Additionally, we use The Rasch measurement model to examine psychometric properties of DASS-21. The results indicate that the DASS-21 fulfills the psychometric measurement aspect by providing evidence as a valid and reliable instrument, with a very good item reliability value .99 and sufficient person reliability (.89), as well as a Cronbach alpha value KR-20. of .91, meaning that the quality of the items is very good for revealing depression, anxiety, and stress. Furthermore, the results are reinforced by the Principal Component Analysis (PCA) value to the residual of 39.7%, meaning that the items in DASS-21 are representative for measuring depression, anxiety, and stress. Therefore, it can be said that the DASS-21 is valid and reliable for assessing the levels of stress, anxiety, and depression. The Indonesian translation of the DASS-21 constructs can also be used to assess the stress, anxiety, and depression levels.